Mayobre, E. "Introducción a América Latina a través de Jorge Guillermo Federico Hegel" - E. Mayobre; Jorge Aurelio Díaz Ardila (Ideas y Valores)
Mayobre, E. "Introducción a América Latina a través de Jorge Guillermo Federico Hegel", Conciencia Activa 21. Caracas, 18 (2007): 49-76.